ChemInform Abstract: Diaryliodonium Salts in Organic Syntheses: A Useful Compound Class for Novel Arylation Strategies. Issue 34 (4th August 2016) - Aradi, Klara; Toth, Balazs L.; Tolnai, Gergely L.; Novak, Zoltan
Abstract: Review: [120 refs.